P109 Can A Theory-informed Interactive Animation Increase Intentions To Engage In Physical Activity In Young People With Asthma?. (10th November 2014) - Hoskins, G; Williams, B; Murray, J; Skar, S; McGhee, J; Gauld, D; Brown, G; Treweek, S; Sniehotta, F; Cameron, L; Sheikh, A; Hagen, S
Abstract : Background: Participation in regular physical activity improves aerobic fitness and well-being. For people with asthma the benefits also include reduced hospital admissions, absenteeism, medication use, and improved ability to cope with the disease. However, although people with asthma can exercise safely, children and young people with asthma are less likely to be physically active than their peers. Integrating the principles of user-centred design and the MRC Framework for Complex interventions a theoretically-informed interactive animation was developed to encourage young people aged 12–18 years with asthma to engage in physical activity. Methods: A mixed-methods two stage approach was used. In stage 1 a user group (young people with asthma, parents, health professionals) used online consultation and discussion methods to inform the development of the intervention in a highly iterative manner (modelling). The theoretical basis for the intervention was then refined and converted into a 3D animation with accompanying action plan and volitional help sheet. In stage 2 a web-based Interactive Modelling Experiment evaluated effectiveness in three key areas: knowledge about asthma, inhaler use, and intention to increase physical activity. One-to-one interviews and focus groups were used to evaluate the acceptability of the animation and whether the theoretical basis was effective. Results: Twenty three people were recruited to the user group. Facilitated by multiple online consultation methods the group was highly engaged throughout. Fifty-three individuals were randomised online to receive the intervention or control; 26 completed follow-up questionnaires (49%). The pilot online experiment supported the evidence base for the intervention but demonstrated that recruitment methods and loss to follow-up need addressed before a future trial. Though not powered to detect an effect on intentions and behaviour, the study revealed an impact on intentions to be active (increase) and on safe inhaler use (decrease). Qualitative feedback was positive across all groups, the intervention being well received and regarded as understandable, meaningful, engaging and potentially very useful within an asthma review. Conclusion: We have developed a high quality, two part intervention regarded as meaningful, acceptable and potentially useful. Future work is needed to establish whether acceptability levels and perceived effectiveness translate into behaviour change.